ELEMENTARY SCHOOL TEACHERS’ AND MATHEMATICS TEACHER CANDIDATES’ UNDERSTANDING OF DIVISION WITH REMAINDERS - Kristoforus Djawa Djong; Meryani Lakapu; Irmina Veronika Uskono; Yohanes Ovaritus Jagom; Wilfridus Beda Nuba Dosinaeng; Samuel Igo Leton (Program Studi PGSD Universitas Flores, 2025)
Mathematics is studied from basic education to higher education. Understanding math concepts is important to learn because it is related to numeracy skills and also to form the basis of understanding at a higher level. One of the important materials to study is division, especially remainder division. This study aims to analyze and compare the understanding of elementary school teachers and prospective mathematics teachers in solving division problems with remainders. This research is a descriptive qualitative. Data were collected through descriptive tests and in-depth interviews with 13 elementary school teachers and 19 mathematics education study program students. The results showed that 92.3% of teachers used the porogapit method in solving the remaining division problems, and the rest used the Gasing method. Meanwhile, 63.16% of student teachers used the porogapit method and the rest showed more method variations. Although student teachers tended to be more thorough in completing the work, errors were still found due to inaccuracy and lack of conceptual understanding. Both groups have not shown a thorough mastery of the concept of remainder division. These findings provide a basis for improving the quality of mathematics learning.